Possibilities for preventive treatment in rheumatoid arthritis? Lessons from experimental animal models of arthritis: a systematic literature review and meta-analysis. Issue 2 (1st August 2016) - Dekkers, J S; Schoones, J W; Huizinga, T W; Toes, R E; van der Helm-van Mil, A H
Abstract : Objective: Current research in rheumatoid arthritis focuses on preclinical disease phases as it is hypothesised that early preclinical treatment might prevent progression to full-blown disease. Since performance of studies in prearthritis phases in humans is challenging, animal models offer an opportunity to evaluate preventive treatments. We performed a systematic literature review and summarised treatment effects during different stages of arthritis development in animal models. Methods: Eight medical literature databases were systematically searched. Studies were selected if they reported effects of synthetic or biological disease-modifying antirheumatic drugs in animal models of arthritis (collagen-induced arthritis and adjuvant-induced arthritis) on arthritis severity, as measured with arthritis severity scores, paw swelling or paw volume. Quality was assessed using an 11-item checklist. Study characteristics were extracted and effect sizes obtained in high-quality studies were summarised in meta-analyses. Studies were categorised into three groups: prophylactic (prior to generation of autoantibody response), prearthritis (after induction of autoantibody response) and therapeutic intervention (after arthritis development). Results: Out of 1415 screened articles, 22 studies (including n=712 animals) were eligible of good quality and included in meta-analyses. Prophylactic (16 experiments, n=312 animals) and prearthritis treatment (9 experiments, n=156 animals) both were associated with a reduction of arthritis severity (p<0.001 and p=0.005, respectively). Stratified analyses for different antirheumatic drugs initiated in the prearthritis phase suggested higher efficacy of methotrexate than of anti-tumour necrosis factor. Conclusions: Data of experimental studies in animal models of arthritis suggest that prophylactic and prearthritis treatment strategies are effective and hint at differences in efficacy between antirheumatic drugs.